Evolutionary constraints on the acquisition of antimicrobial peptide resistance in bacterial pathogens. Issue 12 (December 2021) - Jangir, Pramod K.; Ogunlana, Lois; MacLean, R. Craig
Abstract : Antimicrobial peptides (AMPs) offer a potential solution to the antibiotic resistance crisis. Recent studies have revealed important evolutionary constraints on the evolution and horizontal spread of AMP resistance in bacteria. Here, we summarize these advances and highlight their importance for therapeutic development of AMPs.